Bladder and Bowel Dysfunction Network: Improving the Management of Pediatric Bladder and Bowel Dysfunction. Issue 2 (10th March 2021) - Pokarowski, Martha; Rickard, Mandy; Kanani, Ronik; Mistry, Niraj; Saunders, Megan; Rockman, Rebecca; Sam, Jonathan; Varghese, Abby; Malach, Jessica; Margolis, Ivor; Roushdi, Amani; Levin, Leo; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: Lower urinary tract symptoms with constipation characterize bladder and bowel dysfunction (BBD). Due to high referral volumes to hospital pediatric urology clinics and time-consuming appointments, wait times are prolonged. Initial management consists of behavioral modification strategies that could be accomplished by community pediatricians. We aimed to create a network of community pediatricians trained in BBD (BBDN) management and assess its impact on care. Methods: We distributed a survey to pediatricians, and those interested attended training consisting of lectures and clinical shadowing. Patients referred to a hospital pediatric urology clinic were triaged to the BBDN and completed the dysfunctional voiding symptom score and satisfaction surveys at baseline and follow-up. The Bristol stool chart was used to assess constipation. Results were compared between BBDN and hospital clinic patients. Results: Surveyed pediatricians (n = 100) most commonly managed BBD with PEG3350 and dietary changes and were less likely to recommend bladder retraining strategies. Baseline characteristics were similar in BBDN (n = 100) and hospital clinic patients (n = 23). Both groups had similar improvements in dysfunctional voiding symptom score from baseline to follow-up (10.1 ± 4.2 to 5.6 ± 3.3, P = 0.01, versus 10.1 ± 4.2 to 7.8 ± 4.5, P = 0.02). BBDN patients waited less time for their follow-up visit with 56 (28–70) days versus 94.5 (85–109) days for hospital clinic patients ( P < 0.001). Both groups demonstrated high familial satisfaction. Conclusions: Community pediatricians may require more knowledge of management strategies for BBD. Our pilot study demonstrates that implementing a BBDN is feasible, results in shorter wait times, and similar improvement in symptoms and patient satisfaction than a hospital pediatric urology clinic.